Time to death and its predictors among adult patients with COVID-19: A retrospective cohort study in Ethiopia - Atamenta, Tegene; Cherie, Amsale; Alemu, Wudma (Frontiers in Epidemiology, 2023)
Abstract Background: Coronavirus disease affected people throughout the globe and is becoming a severe threat to the health and wellbeing of the global community. Time to death and predictors of mortality vary across setting .So far, no or little related study has been undertaken in Ethiopia. Studying time to death from COVID-19 and its predictors is essential to understand the characteristics of the diseases and thereby contribute to the identification of indicators for early detection and initiation of treatment. Therefore, this study aimed to estimate time to death and its predictors among adults with COVID -19 in Ethiopia. Methods: A retrospective follow-up study was conducted among 602 adults with COVID-19 attending Eka Kotebe General Hospital, COVID-19 Treatment Center, from March 13, 2020, to November 13, 2020. The data were entered by Epi- data version 4.2 while analysis was carried out using STATA version-16. A Kaplan Meier survivor curve was computed to estimate the survival probabilities. A Log-rank test was used to compare the difference in survival curves. Cox proportional hazard models were fitted to identify predictors of time to death. Results: The overall median time to death was 21 days. Older adults(≥65year) (AHR:2.22,95%CI:1.02,4.86), being Men (AHR:3.04,95%CI:1.61, 5.74), shortness of breathing at admission (AHR:2.29,95%CI:1.16,4.54),comorbidity (AHR: 2.23, 95%CI:1.04, 4.80),diabetes mellitus (AHR 2.31,95%CI:1.30,4.08), altered cardiac function (AHR: 2.07, 95%CI: 1.21, 3.43) and baseline white blood cell count of greater than 10 (103/µL) (AHR 2.62, 95%CI: 1.55, 4.44) were independent predictors of COVID-19 mortality. Conclusion: Male sex, older adults, shortness of breathing at admission, patients with comorbidities, and higher blood cell count were significant predictors of time to death from COVID -19. Therefore, concerned stakeholders should focus on those predictors of mortality and design interventions accordingly to enhance the survival of COVID-19 patients. Keywords: - Time to death, predictors, COVID-19, Ethiopia